Status of major and trace elements in grazing cattle and buffaloes of red laterite and new alluvial zone of West Bengal - DAS, A; GHOSH, T K; HALDAR, S (The Indian Journal of Animal Sciences, 2014)
A survey was carried out in the red laterite and new alluvial zone of West Bangal to compare the status of major (Ca and P) and trace (Fe, Cu, Mu and Zu) elements in grazing cattle and buffaloes. Concentrations of Fe, Cu, Mu and Zu in soil were above the minimum critical concentrations in both the agroclimatic zones. However, 100% of the samples of paddy straw were deficient in Ca, P and Mn in both the zones. Cu defieiency was also widerpread in various concentrate feeds, paddy straw and green roughage. Plasma concentrations of these major and trace elements did not indicate dificiency either in cattle or in buffaloes. No significant difference could be observed between cattle and buffaloes in the plasma concentrations of these mineral elements excep Mn, which was slightly higher (P